Uterine Myoma Position-based Radiofrequency Ablation (UMP-b RFA): 36 months follow-up clinical outcomes. (February 2023) - Fasciani, Alessandro; Turtulici, Giovanni; Pedullà, Alessio; Sirito, Rodolfo
Abstract: Objective: To assess the efficacy of Uterine Myoma Position-based Radiofrequency Ablation (UMP-b RFA) at 36 months. An analysis of a new uterine fibroid ablation technique that allows personalized access of delivering radiofrequency energy (transvaginal, hysteroscopic or laparoscopic) based on myoma localization. Study Design: Prospective observational cohort study in a community-based secondary care medical center enrolled 61 premenopausal women with 112 symptomatic uterine myomas. 112 fibroids were ablated in 5 ways with single or combined accesses: 82 Vaginal Ultrasound (VU)-guided RFA, 19 Laparoscopic (L)-RFA, 5 Hysteroscopic (H)-RFA, 5 VU+H-RFA, and 1 VU+L-RFA. The primary endpoint of this study was to evaluate the 3-year clinical outcome of UMP-b RFA. The secondary endpoint was the possible identification of predictors of its success. The outcomes evaluated at 12, 24, and 36 months after UMP-b RFA were myoma size, type of symptomatology suffered, quality of life based on the "Uterine Fibroid Symptom and Quality of Life" questionnaire, and interviews on the degree of satisfaction with this surgery. The reintervention and complication rates were also recorded and analyzed. Results: Fibroids volume and diameter were significantly reduced by −90.2 % / −55.7 % at 36 months post-intervention (p < 0.001) and the reduction of Symptom Severity scores was −71.8 % three years after UMP-b RA (p < 0.001). The overall improvement in the quality of life was demonstrated by an increase in the Quality-of-Life score of + 26.0 % at the third follow-up (p < 0.001). 88.5 % of the patients interviewed would have the surgery done again if they went back in time. The reintervention rate was 10/61 (16.4 %): 3 hysterectomies, 3 myomectomies, 3 operative hysteroscopies and 1 VU-RFA reoperation. In this group of unsuccessful surgeries, the mean diameter of the dominant myomas was found to be greater than that of the successes (5.3 vs 4.4 cm.). Out of the 61 cases, no major complications occurred, and the 2 minor complications observed were self-limiting. Conclusion: Uterine Myoma Position-based Radiofrequency Ablation is a safe, effective, and minimally invasive solution for the treatment of symptomatic fibroids. Indeed, these clinical outcome data at 36 months shows how UMP-b RFA can treat the symptomatology of uterine fibromatosis. Hysterectomies or myomectomies were successfully avoided in more than 80 % of women bearing myomas with an average diameter of less than 5 cm.